ANALISA PERBANDINGAN DAYA DUKUNG FONDASI BORED PILE DAN TIANG PANCANG DENGAN MENINJAU POTENSI LIKUIFAKSI - Rinda Karlinasari (Pondasi, 2022)
AbstractThe foundation is part of the building structure which has the function of transmitting the load into the ground which is strong enough to support the structure above it. Soil conditions in Indonesia have the potential for liquefaction to occur which is a problem in the planning foundation, due to the increasing change in soil granules from a solid state (solid) to liquid (liquid). The purpose of this Final Project is to determine the liquefaction potential that occurs and determine the comparison of the efficiency of using the foundation from the soil carrying capacity. In this analysis, liquefaction assistance uses the CSR (Cyclic Stress Ratio), CRR (Cyclic Resistance Ratio) and Liquifaction Potential Index (LPI) methods. Manual calculation of the bearing capacity comparison of the axial clearance using the Reese and Wright, Mayerhoff method, for Lateral using the Broom method and calculations using the ALLPILE application. The collection methodology uses secondary data obtained from the project and conducts literacy studies. The calculation results for the discovery of liquefaction potential using SPT data at a depth of 14-19 m and a depth of 26-27 m have an FS value < 1, causing a liquefaction potential. The calculation of the LPI value in the SPT data has a severity level in the Low category because the LPI value is 0 < LPI < 5. Manual calculation of Qall Bored Pile and Pile foundations at a depth of 21 m using the Reese and Wright and Mayerhoff methods, obtained the average result of manual calculation of the foundation bore pile of 2382.95 kN, while the pile foundation of 1678.97 kN. So that the carrying capacity of the Bored Pile foundation permit is 29.54% greater than the Pile. Comparison of manual calculations with ALLPILE for Bored Pile foundations is 11.53% greater than manual calculations, for Pile foundations it is 38.55% greater than manual calculations. From the results of the comparison of the two foundations, the BorePile foundation is more efficient, because of the permit carrying capacity which is quite dominant, it is larger than the Pile.Keywords: Liquefaction, Foundation Bearing Capacity, Comparison of Bored Pile Foundation Bearing Capacity; Pile.AbstrakFondasi adalah bagian dari struktur bangunan yang memiliki fungsi untuk meneruskan beban ke dalam tanah yang cukup kuat untuk mendukung struktur diatasnya. Kondisi tanah di Indonesia memiliki potensi terjadinya likuifaksi yang menjadi permasalahan pada perencanaan fondasi, karena meningkatkan perubahan butiran tanah dari keadaan padat (solid) menjadi cairan (liquefied). Tujuan dari Tugas Akhir ini adalah mengetahui potensi likuifaksi yang terjadi dan menentukan perbandingan Efisiensi penggunaan fondasi dari nilai daya dukung tanah.Dalam analisa ini, identifikasi likuifaksi menggunakan metode CSR (Cyclic Stress Ratio), CRR (Cyclic Rasistance Ratio), dan Liquifaction Potential Index (LPI). Perhitungan manual perbandingan kapasitas daya dukung ijin aksial menggunakan metode Reese and Wright, Mayerhoff, untuk Lateral menggunakan metode Broom dan perhitungan menggunakan aplikasi ALLPILE. Metodologi pengumpulan menggunakan data sekunder yang didapat dari pihak proyek dan melakukan studi literasi.Hasil perhitungan identifikasi potensi likuifaksi menggunakan data SPT pada kedalaman 14-19 m dan kedalaman 26 – 27 m memiliki nilai FS < 1 sehingga menyebabkan potensi likuifaksi. Perhitungan nilai LPI pada data SPT mempunyai tingkat keparahan dengan kategori Low karena nilai LPI 0 < LPI < 5. Perhitungan manual Qall fondasi Bored Pile dan Tiang Pancang pada kedalaman 21 m menggunakan metode Reese and Wright dan Mayerhoff, didapat hasil rata-rata perhitungan manual fondasi bore pile sebesar 2382,95 kN, sedangkan fondasi Tiang Pancang sebesar 1678,97 kN. Sehingga daya dukung ijin fondasi Bored Pile lebih besar 29,54 % dibandingkan Tiang Pancang. Perbandingan Perhitungan manual dengan ALLPILE fondasi Bored Pile lebih besar 11,53% dari perhitungan manual, untuk fondasi Tiang Pancang lebih besar 38,55% dari perhitungan manual. Dari hasil perbandingan kedua fondasi, fondasi BorePile lebih efisien, karena dari daya dukung ijin yang cukup dominan lebih besar daripada Tiang Pancang.Kata Kunci : Likuifaksi, Daya Dukung Fondasi, Perbandingan Daya Dukung fondasi Bored Pile ; Tiang Pancang.